The Effect of Problem-Based Learning on Junior High School Students’ Mathematical Problem-Solving Ability: A Meta-Analysis - Luluk Murniati; Muhammad Fachri B Paloloang; Baharuddin Baharuddin; Mubarik Mubarik (Edumatika, 2026)
Background: Mathematical problem-solving ability remains a major challenge among junior high school students, while empirical studies on the effectiveness of Problem-Based Learning (PBL) have reported inconsistent findings. Purpose: This study aims to synthesize evidence of PBL effectiveness on junior high school students’ mathematical problem-solving ability. Method: Through meta-analysis following PRISMA procedures, 14 eligible studies published between 2016 and 2025 were identified, while 11 studies used for further analysis. Comprehensive Meta-Analysis (CMA) software was used to determine effect sizes, heterogeneity, publication bias, and moderator variables. Findings: The results showed that PBL has a medium effect size (g = 0.569; p < 0.001) with stronger effect in Grade VIII, topics requiring HOTS, and during the COVID-19 studies. Heterogeneity was moderate, while publication bias and sensitivity tests confirmed results’ robustness. Implications: These findings support the use of PBL in mathematics learning to enhance students’ mathematical problem-solving ability across diverse classroom settings. Originality: This study contributes a quantitative synthesis of PBL effectiveness and highlights factors influencing its impact on mathematical problem-solving ability.